2017
DOI: 10.2337/dc16-1990
|View full text |Cite|
|
Sign up to set email alerts
|

Factors Associated With Diabetes-Specific Health-Related Quality of Life in Youth With Type 1 Diabetes: The Global TEENs Study

Abstract: OBJECTIVEOur objective was to characterize diabetes-specific health-related quality of life (D-HRQOL) in a global sample of youth and young adults with type 1 diabetes (T1D) and to identify the main factors associated with quality of life.RESEARCH DESIGN AND METHODSThe TEENs study was an international, cross-sectional study of youth, 8–25 years of age, with T1D. Participants (N = 5,887) were seen in clinical sites in 20 countries across 5 continents enrolled for 3 predetermined age groups: 8–12, 13–18, and 19–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
129
4
30

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(170 citation statements)
references
References 30 publications
7
129
4
30
Order By: Relevance
“…Yeh in her systematic review and meta‐analysis with randomized controlled trials also concluded that CSII and MDI have similar effects on GC in children and adolescents. We found that male adolescents had better HRQoL that is in line with the literature …”
Section: Discussionsupporting
confidence: 92%
“…Yeh in her systematic review and meta‐analysis with randomized controlled trials also concluded that CSII and MDI have similar effects on GC in children and adolescents. We found that male adolescents had better HRQoL that is in line with the literature …”
Section: Discussionsupporting
confidence: 92%
“…More studies are needed to find effective interventions for girls. An ongoing study is presently being conducted evaluating educating young females individually with GSD‐Y …”
Section: Discussionmentioning
confidence: 99%
“…Support can be constructive or destructive and affects the adolescent's ability to self‐manage the disease . Parents' ability to cooperate seems to affect both family conflicts and glycaemic control . Adolescents who experience a more positive tone in conversations with their parents also have a better glycaemic control .…”
Section: Discussionmentioning
confidence: 99%
“…A Rapid and dynamic cognitive, developmental, and emotional changes occur during childhood, adolescence, and emerging adulthood. Diabetes management during childhood and adolescence places substantial burdens on the youth and family, necessitating ongoing assessment of psychosocial status and diabetes distress during routine diabetes visits (10)(11)(12)(13)(14). Early detection of depression, anxiety, eating disorders, and learning disabilities can facilitate effective treatment options and help minimize adverse effects on diabetes management and disease outcomes (15).…”
Section: Psychosocial Issuesmentioning
confidence: 99%